Enhancing Educational Systems on Creating Job Opportunities by Promoting Knowledge-Based Economy in the Sultanate of Oman - NourEldin Mohamed Elshaiekh; Said Mohammed Alrashdi; Ahmed Maher Shehata; Naifa Eid Bait bin Saleem (Qubahan Academic Journal)
Education is the foundation of progress, development, and the growth of individuals and societies. Knowledge-based education plays a significant role in enhancing educational systems, resulting in improved learning outcomes, enriched knowledge, job creation, and reduced unemployment. It also supports the alignment between educational outcomes and labor market needs by continuously adapting to innovations and advancements. In Oman, the educational system is governed and developed using modern technologies, in alignment with Oman Vision 2040. This research outlines strategies and methods to strengthen knowledge-based education in Oman, with the goal of reducing unemployment and providing suitable job opportunities for Omanis across various sectors. This approach heavily depends on the production and utilization of knowledge and information as key resources for economic growth, addressing gaps and shortcomings in the application of the knowledge economy. The proposed model involves leveraging technology, improving education, and fostering research and development with modern technologies and artificial intelligence tools to enhance educational systems and generate employment opportunities. The study aims to explore how education can contribute to reinforcing the knowledge economy in Oman by advancing educational systems and creating new jobs, focusing on the challenges and opportunities within the framework of Oman Vision 2040, which seeks to achieve sustainable economic growth. Additionally, the research discusses differences in averages among respondents' educational qualifications, with the highest average recorded for PhD holders at approximately 4.5% that holders of these qualifications are the ones who can be relied upon to convey and disseminate the culture of the knowledge economy among university and college students. The lowest for diploma holders is at less than 4.2%. The statistical significance (sig.) of the distribution of differences between groups was 0.926% for the first item, 0.601% for the second item, and 0.019% for the third item. The F-statistic in the ANOVA analysis revealed varying percentages, indicating different impacts of the studied factors on improving education and promoting the knowledge economy in Oman.